Avoiding Small Monochromatic Distances - Waknine, Tom (The PUMP Journal of Undergraduate Research, 2022)
Is it true that for any coloring of the points of R in two colors there is an ε >0 such that one of the color classes contains pairs of points at every distance smaller than ε ? We show that the answer to this question is no.